ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV SD 6 KANDANGMAS DITINJAU DARI GAYA BELAJAR - Fevironika, Dona Oktaviani; Fajrie, Nur; Wanabuliandari, Savitri (IKIP Siliwangi Bandung, 2023)
This research aims to analyze the difficulty of learning mathematics in terms of students' learning styles. This study uses a qualitative descriptive research design with a case study approach. In this study the subjects used were all students of grade IV, totaling six students. Data collection techniques in this study were observation, questionnaires, interviews and documentation. The data analysis technique uses a qualitative approach using the Milles & Huberman model including the stages of data reduction, data presentation, and drawing conclusions. The results showed that the learning styles obtained by fourth grade students at SD 6 Kandangmas were 1 student with a visual learning style, 3 students with an auditory learning style, and 2 students with a kinesthetic learning style. Students with a visual learning style have difficulty learning mathematics in terms of weaknesses in counting and transferring knowledge, students' difficulties in learning mathematics with an auditory learning style tend to experience difficulties in all indicators, this indicates that students with an auditory learning style experience various difficulties. subject difficulties include aspects of weakness in arithmetic, difficulties in transferring knowledge and errors in visual perception, while students with a kinesthetic learning style experience difficulties in learning mathematics in aspects of weakness in arithmetic and transferring knowledge.